2018
DOI: 10.1111/efp.12435
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of pine mistletoe on the growth of Scots pine

Abstract: Summary Mistletoe infection results in substantial growth losses in mistletoe‐infected forests. This study reports and evaluates the results of retrospective analyses of radial growth of Scots pine (Pinus sylvestris) in relation to the level of infection of pine mistletoe (Viscum album ssp. austriacum). A total of 43 Scots pine trees were destructively sampled from different sites. Of these trees, 14 were uninfected and 29 were infected. Infection classes were determined using six‐class dwarf mistletoe rating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
1
23
0
2
Order By: Relevance
“…Nutrients absorbed by trees-macroelements N, K, Ca, P, and S and trace elements Mg, Fe, Cu, Zn, Mo, B, Na, and N-accumulate in mistletoe, making them inaccessible to the host, especially in needles, increasing the adverse impact of drought [57]. It was found that the total chlorophyll content in pine needles affected by mistletoe increased from April to June, then decreased to September, whereas in healthy plants it increased from April to October [56]. In needles of infected pines, the decrease in chlorophyll content resulted in a decrease in photosynthetic efficiency and damage to chloroplasts resulted from Fe + deficiency [57].…”
Section: Viscum Biology and Host Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrients absorbed by trees-macroelements N, K, Ca, P, and S and trace elements Mg, Fe, Cu, Zn, Mo, B, Na, and N-accumulate in mistletoe, making them inaccessible to the host, especially in needles, increasing the adverse impact of drought [57]. It was found that the total chlorophyll content in pine needles affected by mistletoe increased from April to June, then decreased to September, whereas in healthy plants it increased from April to October [56]. In needles of infected pines, the decrease in chlorophyll content resulted in a decrease in photosynthetic efficiency and damage to chloroplasts resulted from Fe + deficiency [57].…”
Section: Viscum Biology and Host Impactmentioning
confidence: 99%
“…Mistletoe infection causes crown thinning by reducing foliage biomass (Figure 3). Bilgili et al [56] reported that needle biomass may be reduced by as much as 40% in infected trees. Decreased chlorophyll content in foliage of infected trees [58,94] leads to significant reduction of photosynthetic capacity [95] and results in growth losses of host trees [96,97].…”
Section: Tree Growth and Economic Losses Caused By Mistletoe And Possmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, evidence from comparisons of P. contorta killed by bark beetles versus those that survived suggests that investing in larger resin ducts is a better defensive strategy for this species than increasing the number of resin ducts [65]. Thus, my findings offer a potential mechanism underlying prior reports of increasing rates of bark beetle attack and pest-related mortality resulting from mistletoe infection (e.g., [24,30,32,33]). My results also highlight the need for additional studies, similar to that of Klutsch and Erbilgin [34], that consider multiple measures of resin defense in pines infected by mistletoe and then work to unravel the various direct and indirect pathways through which abiotic and biotic factors shape these defenses in conifers.…”
Section: Discussionmentioning
confidence: 57%
“…The indirect negative effect of mistletoe infection on resin duct defenses, which results from the suppression of tree growth by mistletoe infection, adds a mechanistic explanation to prior reports of lower growth rates and higher mortality linked to mistletoe infection level [21,22,[25][26][27][28][29][30]32,33]. Given that bark beetles are more likely to attack and kill trees with fewer or smaller resin ducts [4][5][6], the suppression of resin duct sizes and total area by mistletoe infection could help to explain the higher rates of attack by bark beetles on pines with severe mistletoe infections [23,24].…”
Section: Hypothesized Direct and Indirect Effects Of Mistletoe On Resmentioning
confidence: 99%